2006
DOI: 10.1128/aem.72.5.3175-3183.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutrient Periodicity on Microbial Community Dynamics

Abstract: When microbes are subjected to temporal changes in nutrient availability, growth rate and substrate affinity can contribute to competitive fitness and thereby affect microbial community structure. This hypothesis was tested using planktonic bacterial communities exposed to nutrient additions at 1-, 3-, 7-, or 14-day intervals. Growth rates after nutrient addition were inversely proportional to the pulse interval and declined from 0.5 h ؊1 to 0.15 h ؊1 as the pulse interval increased from 1 to 14 days. The dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 48 publications
5
39
0
1
Order By: Relevance
“…Konopka et al (45) studied 16 replicate microcosms subject to discrete pulses of gelatin every day and every 7 days and observed very dynamic bacterial communities, although they observed greater variability between their replicates than we did. Similar perturbation studies (46, 47) concluded that internal dynamics seemed to dominate and external forcing was not a strong selective pressure, which is consistent with our findings. Analysis of natural marine communities during a phytoplankton bloom also displayed rapid replacement of the dominant organisms and the importance of internal feedbacks in shaping communities (34).…”
Section: Discussionsupporting
confidence: 93%
“…Konopka et al (45) studied 16 replicate microcosms subject to discrete pulses of gelatin every day and every 7 days and observed very dynamic bacterial communities, although they observed greater variability between their replicates than we did. Similar perturbation studies (46, 47) concluded that internal dynamics seemed to dominate and external forcing was not a strong selective pressure, which is consistent with our findings. Analysis of natural marine communities during a phytoplankton bloom also displayed rapid replacement of the dominant organisms and the importance of internal feedbacks in shaping communities (34).…”
Section: Discussionsupporting
confidence: 93%
“…The Proteobacteria were the predominant group in our investigation, accounting for 45 (50%) of 90 sequences, consistent with other investigations reporting high prevalence (20-50%) of Proteobacteria in bacterial communities in aquatic habitats [2,3,18] such as seawater [15,33], decaying salt marsh grass [7], and wastewater [7]. In potable water distribution systems, many bacterial species, including members of the Proteobacteria, Actinobacteria, low-G+C-content gram-positive bacteria, and Cytophaga-Flavobacterium-Bacterioides group, readily adhere to surfaces to form multispecies biofilms [39].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings therefore suggest that even after a very long adaptation period, recurrent changes in the physicochemical conditions at the wetland surface prevent the formation of a stable microbial community. In agreement with this, Carrero-Colón et al (2006) reported that even after 130 days, no stable community structure developed at any pulse interval when an energy source was periodically added to a complex microbial community. We acknowledge that the observed changes might also have been caused by other seasonally varying environmental factors and note that, as always with open 'natural' systems, it can be impossible to incorporate suitable negative controls.…”
Section: Discussionmentioning
confidence: 58%